Intercultural Learning: Critical preparation for international student travel - Peter Jones (UTS ePRESS, 2018)
International student exchanges are an increasingly popular aspect of the internationalisation of higher education around the globe. Whether as short-term mobility projects or semester long 'study abroad' opportunities, the benefits of such international study experiences have been well documented. Higher education institutions, departments and disciplines, or individual academics are often tasked with preparing students for such international experiences. Such preparation often focuses on the practical and logistical aspects of student travel, overlooking a crucial dimension of student learning. Intercultural learning: Critical preparation for international student travel aims to take students beyond practical preparation, to equip them with a critical lens through which to view and understand their international experiences. The book leads students toward a deeper understanding of culture and cultural difference through an exploration of challenging concepts such as imperialism, racism, privilege and intercultural practice. As an adjunct to traditional approaches, the book adds a significant and valuable dimension to the process of preparing students for international study, increasing the potential for meaningful and transformative learning experiences.